PECULIARITIES OF THEATRICAL ART (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2021)
It is known that art has been a means of education for goodness, enrichment of the spiritual world, communication with each other, and even a way of life since the formation of human consciousness.This article discusses the specific features, purpose and importance of theatrical art in the formation of man.